دراسة أثر تسويق الخدمات المصرفية على سلوك العملاء بالتطبيق على المصارف العامة في محافظة اللاذقية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدف هذا البحث إلى دراسة واقع عناصر مزيج التسويق المصرفي في المصارف العامة في محافظة اللاذقية، ودور هذه العوامل في جذب العملاء من السوق وتشجيعهم للتعامل مع هذه المصارف لا سيما وأن عناصر المزيج التسويقي تعتبر من أهم العوامل المؤثرة في سلوك العملاء، الأمر الذي يحتم على إدارات المصارف ضرورة الاهتمام بتسويق الخدمات المصرفية بشكل منظم ومدروس. وانطلاقا من هنا، فقد تم على ضوء الدراسة الميدانية التي تم إجراؤها التوصل إلى مجموعة من النتائج والتوصيات التي من الممكن في حال استخدامها المساهمة في تفعيل دور التسويق المصرفي وتحسين معدلات أداء مصارفنا العامة لاسيما بعد تزايد حدة انفتاح سوقنا المصرفية على السوق العالمية. This research aims to study the reality of the mix of bank marketing elements in the public banks in Latakia , and the role of these elements in attracting customers encouraging them to deal with these banks.  The elements of marketing mix are considered one of  the most important factors which affect the customers behavior . This will make it necessary for all the banks to be interested in marketing the bank services in a well–organized and well–studied manner . For this reason, in the light of the field research we have done, many results and recommendations have been reached. If these results and recommendations are utilized, there will be a contribution in activating  the role of the bank marketing and improving the rates of working in our public banks .